Ovarian development and the reproductive profile of Astyanax altiparanae (Teleostei, Characidae) over one year: Applications in fish farming - Cassel, Mônica; Chehade, Chayrra; Souza Branco, Giovana [UNESP]; Caneppele, Danilo; Romagosa, Elizabeth; Borella, Maria Inês (Elsevier, 2017)
Astyanax altiparanae is a Brazilian species of substantial commercial, environmental and scientific importance; however, existing studies on its reproduction do not seem to provide enough details. In light of the increasing use of this species in fish farming and the need for basic studies for the development of new production technologies, we describe the structural and ultrastructural characteristics of the ovaries of A. altiparanae, and characterize the species' reproductive cycle. Females were collected monthly from March 2013 to February 2014, and reproductive management began in October 2013. The ovaries were removed, fixed in Karnovsky's fixative, and prepared for light microscopy, transmission electron microscopy and immunohistochemistry anti-PCNA. These techniques enabled us to characterize the ovaries, the germ cells, and the somatic cells in detail, as well as their changes over time. The reproductive cycle was characterized based on the monthly variation in the gonadosomatic ratio, the proportion of germ cells, and the rate of oogonium proliferation. The macroscopic analysis of the ovaries suggests that the vascularization pattern and color of the ovaries vary according to development. There are new types of analyses that can be applied even in the fish farming industry, such as a comparison between ovaries staining and weight or the frequency distribution of these colors throughout the year. This study also provides details on microscopic characteristics that have never before been reported for species of Astyanax, such as the presence of annulate lamellae in oogonia, the development of the zona pellucida from oocytes in the one-nucleolus step, and the development of the micropylar apparatus in oocytes in the cortical alveolar step. When the reproductive cycle was analyzed, this species was found to have a long period of spawning, with a reproductive peak from October to February and multiple spawning events, confirming the period already described in the literature. Variations in reproductive periods and the ability to reproduce in lentic environments suggest that A. altiparanae has the ability to respond quickly to environmental changes and exhibits high reproductive flexibility. All of these characteristics confirm the great potential of this species in the fish farming industry.
Keywords: Fish production; Germ cell proliferation; Histology; Reproductive management; Reproductive migration; Ultrastructure